Cystatin C: A Better Predictor of Kidney Function in Diabetic Patients (Bangladesh Journal of Medical Biochemistry, 2013)
Serum cystatin C is a new promising marker of renal function. The aim of this study was to analyze serum cystatin C as a better predictor of renal function in diabetic nephropathy. In 60 diagnosed diabetic patients, serum cystatin C and serum creatinine were assessed. Glomerular filtration rate was estimated based on the cystatin C concentration according to Cockcroft- Gault formula and based on serum creatinine concentration according to Larsson formula. DTPA-GFR (Diethylenetriamene pentaacetate Renogram) was done as reference standard. The cross tabulation of DTPA-GFR was done with eGFR- creatinine and eGFRcystatin C. The calculated sensitivity, specificity and accuracy of eGFR- creatinine were 85%, 87.2% and 85% respectively. The eGFR- cystatin C showed higher sensitivity, specificity and accuracy than eGFR- creatinine in studied diabetic subjects. The cystatin C showed more significant correlation, r=0.78, p